2005
DOI: 10.1002/pts.679
|View full text |Cite
|
Sign up to set email alerts
|

Canadian bag‐in‐box wine under distribution channel abuse: material fatigue, flexing simulation and total closure/spout leakage investigation

Abstract: Bag-in-boxUp to 60% of total O 2 ingress in BIB is caused by the tap, an element overlooked by actual standards. 10-16% of tap permeation was due to the neck and valve-neck interface, and the snugness of the fit was particularly sensitive to temperature under our experimental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…This indicates that minimizing the movement of a wine assists in retaining higher levels of alcohol and overall wine aroma. Doyon et al (2005) have shown that storage duration and temperature affect oxygen permeation more than mechanical movement does. Butzke et al (2012) have shown that transportation can cause a bottle aging effect on wine of between 1 and 18 months more than that on wine stored at cellar temperatures.…”
Section: Effects Of Temperature and Vibration During Shipmentmentioning
confidence: 99%
“…This indicates that minimizing the movement of a wine assists in retaining higher levels of alcohol and overall wine aroma. Doyon et al (2005) have shown that storage duration and temperature affect oxygen permeation more than mechanical movement does. Butzke et al (2012) have shown that transportation can cause a bottle aging effect on wine of between 1 and 18 months more than that on wine stored at cellar temperatures.…”
Section: Effects Of Temperature and Vibration During Shipmentmentioning
confidence: 99%
“…Another study [8] indicated that storage time and temperature are more important for oxygen permeation than mechanical movement.…”
Section: David Publishingmentioning
confidence: 99%
“…The most widely used method to evaluate the performance of packaging systems subjected to distribution vibrations, which is often judged by using a simple pass–fail criterion at the completion of each vibration test, is restricted to visual inspection . This provides a very limited means for optimization, which requires a quantitative measure of the level of damage within the system as a function of time.…”
Section: Structural Integrity Monitoring Techniquesmentioning
confidence: 99%